Insight in the phenomena included in loss of the activation of industrial hydrotreating catalyst through an innovative accelerated deactivation procedure and kinetic modeling - Abbas Roshanaei; Sorood Zahedi Abghari; Sepehr Sadighi; Seyed Reza Seif Mohaddecy (Fuel Processing Technology)
An innovative accelerated experimental procedure was developed to study the activity loss of a bifunctional gasoil hydrotreating (GHT) catalyst in a Bench-Scale fixed bed reactor system. This procedure aimed to estimate the impact of coke formation throughout the catalyst's lifespan, from fresh to fully deactivated. Experiments were conducted over 3500 h using a NiMo catalyst to measure the conversion decrease of sulfuric, nitrogenic, and aromatic compounds, indicating catalyst activity loss in hydrotreating reactions. The initial study examined how temperature, pressure, liquid hourly space velocity (LHSV), and hydrogen-to-hydrocarbon ratio affected catalyst deactivation. Results showed that hydrodenitrogenation (HDN) was most impacted by deactivation, while hydrodesulfurization (HDS) was affected to a lesser extent (about one-third of HDN), and hydrodearomatization (HDA) exhibited an intermediate effect. Thermo-Gravimetric Analysis (TGA) revealed that about 20 % of the coke on the deactivated catalyst consisted of volatile matter trapped in the pores. Approximately 60 % of the coke decomposed between 300 °C and 660 °C, while the remaining residue decomposed at higher temperatures. To identify key operating variables affecting catalyst activation loss, intrinsic and apparent kinetic models together with different deactivation functions were developed and fine-tuned. Statistical analysis confirmed that accumulated feed flow rate was the most significant factor in catalyst deactivation.